2010
DOI: 10.1007/s10151-010-0635-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection of colorectal cancer: matched comparison in elderly and younger patients

Abstract: Short-term results after laparoscopic colorectal surgery for cancer in patients ≥75 years old reveal that they have higher postoperative risk compared to their younger counterparts, even when matched by ASA score and type of operation. It suggests that although advanced age, per se, is not a contraindication, it is a risk for patients who undergo laparoscopic colorectal surgery for cancer. This surgery in elderly patients should be performed by experienced surgeons in specialized centers to keep postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…There were many reports of the advantages of laparoscopic colorectal surgery in elderly patients, and studies show that it can be safely performed in very old patients with colorectal cancer [910111213]. …”
Section: Introductionmentioning
confidence: 99%
“…There were many reports of the advantages of laparoscopic colorectal surgery in elderly patients, and studies show that it can be safely performed in very old patients with colorectal cancer [910111213]. …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, complications, particularly those related to advanced age, and 30-day mortality have paramount significance. Although the results of recent studies evaluating whether or not postoperative morbidity and mortality are increasing with advancing age have been controversial, a multicenter analysis of 8,077 colorectal cancer patients operated on with conventional or laparoscopic techniques has shown that age is a significant risk factor for early postoperative mortality [1,12,17,23,24]. The results of the present study suggest that laparoscopic surgery in the elderly is as safe as in younger patients with regard to postoperative complications and early mortality.…”
Section: Discussionmentioning
confidence: 56%
“…Although laparoscopy has been shown to be effective and safe in patients with colorectal cancer, it remains unclear whether or not this technique has any advantages in elderly patients [7,14,15,17,[20][21][22]. Several studies have been conducted in order to assess the feasibility of laparoscopic colorectal surgery in the elderly both for cancer and for benign disease, and reported the results of comparisons with either younger patients who underwent laparoscopic surgery or elderly patients who underwent conventional operations [12,14,16,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that laparoscopic colorectal surgery in older patients is safe and feasible. Fiscon et al 12 compared postoperative outcomes between matched two groups of people ≥75 years (n=50) and 75 (n=50). The study showed more postoperative complications in older patients, even when matched by ASA score and type of operation.…”
Section: Discussionmentioning
confidence: 99%